Solutions of the Maxwell equations describing the spectrum of hydrogen - Simulik, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtain a new class of solutions of the Maxwell equations describing the spectrum of hydrogen. We prove that, instead of the quantum-mechanical Dirac equation, the ordinary classical Maxwell equations can be applied to the solution of many problems in atomic and nuclear physics.